2019
DOI: 10.3390/molecules24112171
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenic Acid and Its Analogs Are Beneficial Physiologic Attenuators in Bdelloid Rotifers

Abstract: The in vivo investigation of kynurenic acid (KYNA) and its analogs is one of the recent exciting topics in pharmacology. In the current study we assessed the biological effects of these molecules on bdelloid rotifers (Philodina acuticornis and Adineta vaga) by monitoring changes in their survival and phenotypical characteristics. In addition to longitudinal (slowly changing) markers (survival, number of rotifers alive and body size index), some dynamic (quickly responding) ones (cellular reduction capacity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The flow injection optimization was performed in order to determine the proper quantifier and qualifier ions of given protonated precursor ions and optimize the collision energy and tube lens for each analyte (Table 1). A six-point curve of the external calibration was used for the quantification of the compounds, which was based on quantifier ion of analyte/quantifier ion of SZR-73 peak area ratios vs concentration [24].…”
Section: Ultrahigh Performance Liquid Chromatography Coupled To Tandementioning
confidence: 99%
“…The flow injection optimization was performed in order to determine the proper quantifier and qualifier ions of given protonated precursor ions and optimize the collision energy and tube lens for each analyte (Table 1). A six-point curve of the external calibration was used for the quantification of the compounds, which was based on quantifier ion of analyte/quantifier ion of SZR-73 peak area ratios vs concentration [24].…”
Section: Ultrahigh Performance Liquid Chromatography Coupled To Tandementioning
confidence: 99%
“…In a recent evaluation, it was found that newly synthetized KYNA analogues can effectively decrease tumor necrosis factor-α (TNF-α) production in Staphillococcus aureus -induced cell cultures [ 220 ]. In another recent evaluation on bdelloid rotifer species, KYNA and its analogs increased longevity, reproduction, and growth in animals, while reducing the capacity and energy-dependent muscular activity at the same time [ 221 ]. Another molecule, 1-methyl-Trp, was found to effectively drive Trp-catabolism toward he KYNA path in both mice and ex vivo human blood cultures [ 222 ].…”
Section: Kynurenines As Biomarkers For Progression and As Possible Therapeutic Targetsmentioning
confidence: 99%
“…24 A similar interdisciplinary regulatory interaction is the effect of kynurenic acid on the metabolism of rotifers. 25 Several studies have proven that this ancient molecule alone prominently and adequately represents the multifunctionality occurring in nature or specific effects on the nervous system. [26][27][28] However, the relevance between micrometazoa and human studies can only be applied and interpreted to a certain extent.…”
Section: Human-related Exceptional Properties Of Rotifersmentioning
confidence: 99%